An Experimental Investigation on the Performance, Combustion and Emission Characteristics of CI Diesel Engine at Various Compression Ratios with Different Ethanol-Biodiesel Blends - Subramanyam Pavuluri, Dr.B.Sidda Reddy, Dr.B.Durga Prasad (International Journal of Advanced Science and Technology, 2020)
In the present scenario of increased industrialization and transportation in the world leads to increased consumption of fossil fuels which in turns leads to depletion of fossil fuels at a faster rate. Fossil fuels combustion is the dominant source for greenhouse gases and global warming. In view of energy crisis raised in 1970’s and environmental concern, many researches are directed towards search of alternative fuels which can replace use of fossil fuels there by reducing pollution. In developing countries like India which is agriculture land the promising bio-fuels are biodiesel and ethanol which are produced from various renewable feedstock like sugarcane, corn etc. and they are also less hazardous to environment because of lower emission property. Ethanol blends results in decreased emissions of hydrocarbon (HC), carbon monoxide (CO) and particulates matter but increase in nitrogen oxides (NOx). Addition of ethanol leads to reduction of biodiesel viscosity. This paper represents variations in the engine parameters like performance, combustion and emission of single cylinder four stroke CI diesel engine by using various compression ratios such as 17.5:1, 18.5:1 and 19.5:1. Experimental research has been conducted with four proportions ethanol, namely E10, E20, E30 and E40. Ethanol-biodiesel mixture mixed with 2% emulsifier 1% diethyl carbonate and 1% ethyl acetate to maintain similarity and to avoid phase separation. Ethanol subjected to high compression ratio has been used to increase brake thermal efficiency (BTE). Increased compression ratio also improves the combustion and performance of the diesel engine.Keywords: Compression Ratio (CR), CI Diesel Engine, Ethanol, Biodiesel, Performance, Combustion, Emissions and Emulsifier.